A Longitudinal Investigation of Moral Injury Appraisals Amongst Treatment-Seeking Refugees - Nickerson, Angela; Hoffman, Joel; Schick, Matthis; Schnyder, Ulrich; Bryant, Richard A.; Morina, Naser (Frontiers in Psychiatry, 2018)
There is currently an unprecedented number of forcibly displaced people worldwide. Understanding psychological mechanisms that contribute to the mental health of refugees and asylum-seekers is important for informing the development of effective interventions for these populations. Moral injury appraisal represents an important potential cognitive mechanism that may contribute to psychological symptoms following exposure to persecution, war and displacement. In the current study, we investigated the longitudinal association between moral injury appraisals related to one’s own perceived transgression (moral injury-self), others’ perceived transgressions (moral injury-other), and PTSD and depression symptoms. Participants in this study were 134 refugees receiving treatment at two outpatient clinics in Switzerland who completed survey measures investigating these concepts. Of these, 71 were followed up two to four years later. Path analyses revealed that greater depression symptoms were associated with subsequent increases in moral injury-self appraisals (β = .25, SE = 0.08, 95% CI [0.11, 0.43], p = .002). In contrast, greater moral injury-self appraisals were associated with subsequent decreases in PTSD symptoms (β = -.23, SE = 0.11, 95% CI = [– 0.44, – 0.31], p = .035). Findings suggest that different types of moral injury appraisals may be associated with differential psychological outcomes. These results have important implications for policy and treatment of refugees and asylum-seekers, highlighting the importance of targeting cognitive factors in the maintenance and treatment of psychological distress, and considering the post-migration context when working with refugees.